Establishing the accuracy of asteroseismic mass and radius estimates of giant stars – II. Revised stellar masses and radii for KIC 8430105. Issue 3 (14th October 2022) - Thomsen, J S; Brogaard, K; Arentoft, T; Slumstrup, D; Lund, M N; Grundahl, F; Miglio, A; Jessen-Hansen, J; Frandsen, S
ABSTRACT: Asteroseismic scaling relations can provide high-precision measurements of mass and radius for red giant (RG) stars displaying solar-like oscillations. Their accuracy can be validated and potentially improved using independent and accurate observations of mass, radius, effective temperature and metallicity. We seek to achieve this using long period SB2 eclipsing binaries hosting oscillating RGs. We explore KIC 8430105, for which a previous study found significant asteroseismic overestimation of mass and radius when compared with eclipsing binary measurements. We measured dynamical masses and radii for both components to be significantly lower than previously established, increasing the discrepancy between asteroseismic and dynamical measurements. Our dynamical measurements of the RG component were compared to corresponding measurements of mass and radius using asteroseismic scaling relations. Uncorrected scaling relations overestimated the mass of the RG by $26{{\ \rm per\ cent}}$, the radius by $11{{\ \rm per\ cent}}$, and the average density by $7{{\ \rm per\ cent}}$, in agreement with studies for other systems. However, using a theoretical correction to Δν, we managed to obtain an asteroseismic average density that is 1σ consistent with our dynamical result. We obtained several measurements of νmax that are not fully consistent. With νmax = 76.78 ± 0.81 $μ$ Hz, the Δν correction provided 2σ consistent mass and radius for the giant. The age of the system was estimated to be 3.7 ± 0.4 Gyr.